2016
DOI: 10.1108/ara-01-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Culture control, capability and performance: evidence from creative industries in Indonesia

Abstract: Purpose The purpose of this study is to investigate the relationship between culture control, capability and creative industries’ performance. Capability which is used in this study is organizational creativity and innovation. Design/methodology/approach This study uses the owner and the manager of creative industries as samples. Total amount of the questionnaires which are used in this data are 270. Data for this study is primary data in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 42 publications
4
36
0
10
Order By: Relevance
“…MCS helps top managers formulate strategies, determine operational actions, implement strategies, clarify expectations, identify priorities for operational improvement, and set targets and improve performance (Simons, 1995). Only a few of the previous studies that observed how MCS was used for the SMEs (Acquaah, 2013;Ismail, 2016), even though around 90% of all businesses around the world were included in the SME sector (Acquaah, 2013). The results of the study conducted by Acquaah (2013) found that dynamic MCS could increase cost efficiency in the SME industry in Ghana.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCS helps top managers formulate strategies, determine operational actions, implement strategies, clarify expectations, identify priorities for operational improvement, and set targets and improve performance (Simons, 1995). Only a few of the previous studies that observed how MCS was used for the SMEs (Acquaah, 2013;Ismail, 2016), even though around 90% of all businesses around the world were included in the SME sector (Acquaah, 2013). The results of the study conducted by Acquaah (2013) found that dynamic MCS could increase cost efficiency in the SME industry in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Henri (2006) reveals that capability was the main attribute for improving performance. Capabilities that can improve the performance of SMEs are creativity and innovation (Ismail, 2016). Creativity and innovation are recognized as the main capabilities which could may contribute significantly to the performance of the firms (Cefis & Marsili, 2006;Matolcsy & Wyatt, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study was conducted by [8], explained the differences between creativity and innovation as follows:…”
Section: Creativity and Innovationmentioning
confidence: 99%
“…Artikel yang membahas tentang ikatan dan hubungan yang terjadi antara sistem akuntansi manajemen dan manajemen strategi yang relatif bersifat baru dan muncul di tahun 1980an (Ismail, 2016). Sementara itu tinjauan mengenai literatur strategi akuntansi sudah dijelaskan oleh berbagai peneliti (Chenhall, 2005).…”
Section: Kajian Teoriunclassified